Mediating Point Defects Endows n‐Type Bi2Te3 with High Thermoelectric Performance and Superior Mechanical Robustness for Power Generation Application. Issue 23 (15th April 2022) - Zhu, Yu‐Ke; Sun, Yuxin; Zhu, Jianbo; Song, Kun; Liu, Zihang; Liu, Ming; Guo, Muchun; Dong, Xingyan; Guo, Fengkai; Tan, Xiaojian; Yu, Bo; Cai, Wei; et al.
Abstract: Bi2 Te3 ‐related alloys dominate the commercial thermoelectric market, but the layered crystal structure leads to the dissociation and intrinsic brittle fracture, especially for single crystals that may worsen the practical efficiency. In this work, point defect configuration by S/Te/I defects engineering is engaged to boost thermoelectric and mechanical properties of n‐type Bi2 Te3 alloy, which, coupled with p‐type BiSbTe, shows a competitive conversion efficiency for the fabricated module. First, as S alloying suppresses the intrinsic B i T e, antisite defects and forms a donor‐like effect, electronic transport properties are optimized, associated with the decreased thermal conductivity due to the point defect scattering. The periodide compound TeI4 is afterward adopted to further tune carrier concentration for the realization of an optimal ZT . Finally, an advanced average ZT of 1.05 with ultra‐high compressive strength of 230 MPa is achieved for Bi2 Te2.9 S0.1 (TeI4 )0.0012 . Based on this optimum composition, a fabricated 17‐pair module demonstrates a maximum conversion efficiency of 5.37% under the temperature difference of 250 K, rivaling the current state‐of‐the‐art Bi2 Te3 modules. This work reveals the novel mechanism of point defect reconfiguration in synergistic enhancement of thermoelectric and mechanical properties for durably commercial application, which may be applicable to other thermoelectric systems. Abstract : Mediating point defects simultaneously modulates the carrier concentration and microstructure in n‐type Bi2 Te3 materials further generating superior thermoelectric and mechanical performance. With high strength and conversion efficiency of over 5% in a wide temperature range, the power generation module fabricated with this n‐type Bi2 Te3 has comprehensive advances compared with commercial modules and may be greatly capable of serving in a hostile environment.